Combined Pathologies in FTLD-TDP Types A and C. Issue 5 (23rd March 2018) - Gefen, Tamar; Ahmadian, Saman S; Mao, Qinwen; Kim, Garam; Seckin, Mustafa; Bonakdarpour, Borna; Ramos, Eliana Marisa; Coppola, Giovanni; Rademakers, Rosa; Rogalski, Emily; Rademaker, Alfred; Weintraub, Sandra; et al.
Abstract: This study investigated the presence of combined pathologies in a large cohort of autopsies that show a primary pathologic diagnosis of phosphorylated 43-kDa TAR DNA-binding protein (FTLD-TDP), the majority of which portrayed clinical phenotypes consistent with primary progressive aphasia or behavioral variant frontotemporal dementia (bvFTD). Thirty-eight cases with FTLD-TDP (30 type-A and 8 type-C) were identified to determine characteristic differences between cases with and without combined pathologies. Findings indicated that combined pathologies co-occur with FTLD-TDP type-A at a high frequency (50%)—greater than when compared to FTLD-TDP type-C cases (12.5%). Those with FTLD-TDP type-A and combined pathologies showed significantly longer lifespans (p < 0.05), and longer disease durations (p < 0.05), than those with only FTLD-TDP type-A. Cases with FTLD-TDP type-A and known genetic mutations tended not to show combined pathology. Those with the GRN mutation and FTLD-TDP type-A showed a significantly younger age of onset (p < 0.05) and younger age at death (p < 0.01) compared to noncarriers. In 1 bvFTD case, we highlight the rare presence of "triple" FTLD-TDP type-A, FTLD-tau, and Alzheimer pathology. The ante- and post-mortem features associated with combined pathologies in FTLD-related disorders are of useful consideration in the stratification of patients to drug trials, and in the development of therapeutic targets for FTLD.